Composition Analysis Of Catches Bubu Tiang During High Tide And Low Tide In Pulau Halang Muka Waters, Kubu Babussalam, Rokan Hilir, Riau - Puput Dewi Sartika; Pareng Rengi; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on Januari 2016 in Pulau Halang Muka Waters, aims to determine difference of catches bubu tiang during high tide and low tide and weight composition and species of catches, using survey method. From the results obtained the highest of catches there at high tide 573590 tail (79,17 kg), while the number of catches on the low tide that is 237666 tail (32,58 kg). Based on the type of species caught are Rebon shrimp (Panaeus mysis) 809600 tail (101,2 kg), White shrimp (Penaeus merguiensis) 1290 tail (1,76 kg), Lomek (Horpodon neherus) 153 tail (2,97 kg), Sword fish (Trichiurus lepturus) 53 tail (0,7 kg), Gulamah (Pseudocienna amovensis) 82 tail (3,49 kg), Giant threadfin (Polynemus tetradactylus) 45 tail (1,15 kg) and Tongue soles (Cynogglossus lingua) 33 tail (0,48 kg).Keywords : Stow net, High tide and Low tide, Pulau Halang Muka Waters